El modelo pedagógico romántico dentro del proceso de enseñanza de los niños de 3 a 5 años - Licto Crespo, Tania Paulina (2022)
The romantic pedagogical model has come to change the paradigms of education with new educational practices, in which students have the ability to express themselves freely in a more effective way in order to promote the well-being of each child. The purpose of the research is to provide an education where children adapt, so it is considered that the romantic pedagogical model is adequate to enrich the educational process; therefore, teachers become mentors, who lead pedagogical leadership according to their interests within the teaching process, allowing students to build their knowledge and share their experiences in joint activities, thus developing creative, reflective thinking and critical, with the ability to easily develop their skills and positively influence academic performance. The teacher must plan activities in order to motivate the child; since it is pursued to prepare them to face and solve problems that arise in daily life; that helps you build better relationships in terms of development and analysis, not only knowing enough, but putting it into practice, the beneficiaries of this work are children, the objective of identifying the characteristics of the romantic pedagogical model within the process of teaching and learning of children from 3 to 5 years of the initial level of the “Vicente León” Educational Unit. The qualitative method was used to help us understand the process based on the investigation and analysis of educational processes, this will allow the development of participatory, collaborative and techniques used to carry out field work, for which the tools designed to collect the same was a survey and the observation sheet. In conclusion, the importance of developing security, independence, self-esteem and relating to the different people in their environment is determined, to solve problems that arise in daily life, it is necessary to resort to bibliographic information, documentaries and the Internet to strengthen knowledge by interacting and allowing children to collaborate in small groups and be able to theoretically support research topics.